Uniśera śatake nabya-Hindu āndolanera kakẏekajana nāẏaka - Rāẏacaudhurī, Sunītirañjana (Ji. E.I. Pābaliśārsa, 1981)
On the role of Bengali intellectuals and social activists in the revival of Hinduism life and Indian nationalism in 19th century Bengal.